IMPLEMENTASI KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH SDN 1 TRI TUNGGAL JAYA - Karla Diana (UNISAN JURNAL, 2024)
This research aims to examine the implementation of managerial leadership by the Principal at SDN 1 Tri Tunggal Jaya and its impact on teacher and student performance. The research method used is descriptive qualitative with research subjects in the form of school principals, teachers and employees. Data was collected through observation, interviews and documentation studies, then analyzed descriptively. The research results show that the implementation of managerial leadership by the Principal at SDN 1 Tri Tunggal Jaya is effective in managing the school. The Principal applies an inclusive approach in managing human resources, provides motivation to teachers and employees, and is active in coaching and training to improve competency. Management of school facilities and infrastructure is also carried out well, including managing the school budget to maximize the use of existing resources. Supporting factors for the implementation of the Principal's managerial leadership include good communication, full support from school members, solid teamwork, and the availability of adequate resources. However, there are also inhibiting factors such as the lack of budget for school development, differences in views and attitudes among school members, as well as policy changes that are not in harmony. The impact of the implementation of the Principal's managerial leadership on the performance of teachers and students at SDN 1 Tri Tunggal Jaya is quite significant. Increasing the quality of learning, student learning motivation, and teacher performance are clear evidence of the effectiveness of managerial leadership. The principal succeeded in creating a conducive learning environment, increasing student interest in learning, and improving teacher performance in carrying out their duties. In conclusion, the implementation of the Principal's managerial leadership at SDN 1 Tri Tunggal Jaya makes a positive contribution in creating a quality learning environment and improving the performance of teachers and students. It is hoped that the results of this research can provide input for school principals and related parties in improving the quality of education in elementary schools. Keywords: